Efektivitas Sun Protecting Factor Serum Ekstrak Biji Pinang (Areca catechu L.) Sebagai Tabir Surya - Sawitri, Satwika Budi; Dewi, Yulisa Raras; Suciati, Anugerah; Agustin, Brillian Sindi (Pusat Penelitian dan Pengabdian Masyarakat Politeknik Harapan Bersama, 2025)
The impact of UV exposure on the skin is to increase the risk of skin cancer, cause sunburn, accelerate premature aging, dark spots and various other skin problems. Based on various research data on the activity of areca nut extract, it can support the development of herbal ingredients for the pharmaceutical and cosmetic industries. The purpose of this study was to determine the effectiveness of areca nut extract serum preparations as sunscreen by calculating the SPF value. The research method used was an experimental method in the laboratory by varying the concentration of areca nut extract in the serum preparation at F0 0%; F1 1.5%; F2 3%; F3 4.5% and F4 6%. The results showed that the extract serum with organoleptic brick red preparations, the distinctive aroma of areca nuts and a semi-solid texture. The resulting pH value ranged from 5.10 to 5.63 with a spreadability of the preparation between 5.13 to 6.07 cm and a viscosity of the preparation in the range of 1363.03 to 4703.03 cPs. The test results on the SPF value showed that F4 had the highest SPF value of 7.088 which was included in the maximum protection category. Based on this study, it can be concluded that the areca nut extract serum in the Oneway Anova test obtained a significance value of 0.05, meaning that there was no significant difference in the SPF activity of each sample. So it can be concluded that the difference in the concentration of areca nut extract in the serum formulation does not significantly affect the sun protecting factor value in the areca nut extract serum preparation.